2022
DOI: 10.1093/europace/euac004
|View full text |Cite
|
Sign up to set email alerts
|

Perceived vs. objective frailty in patients with atrial fibrillation and impact on anticoagulant dosing: an ETNA-AF-Europe sub-analysis

Abstract: Aims Frailty is common in patients with atrial fibrillation (AF), with possible impact on therapies and outcomes. However, definitions of frailty are variable, and may not overlap with frailty perception among physicians. We evaluated the prevalence of frailty as perceived by enrolling physicians in the Edoxaban Treatment in Routine Clinical Practice for Patients With Non-Valvular AF (ETNA-AF)-Europe registry (NCT02944019), and compared it with an objective frailty assessment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Negative perceptions linked to the term "frail" have been previously described and are associated with administrations of treatments that do not follow standard of care. 51,52 It is therefore possible the observed risk of stroke could be due to less intensive prevention efforts in these patients. We would like to note that genetic analysis overcomes these limitations of observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…Negative perceptions linked to the term "frail" have been previously described and are associated with administrations of treatments that do not follow standard of care. 51,52 It is therefore possible the observed risk of stroke could be due to less intensive prevention efforts in these patients. We would like to note that genetic analysis overcomes these limitations of observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, 22 each of the 109 frailty-related International Classification of Diseases, Tenth Revision, codes were assigned a weight ranging from 0.1 to 7.1, depending on its strength of the association with frailty (see the definition of HFRS in Table S1). The HFRS was calculated by summing all weighted points from each code, and the cohort was categorized into low (<5), intermediate (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and high (>15) risk of frailty. 22 To study a cohort of frail patients with AF, we excluded patients with low frailty risk and patients <50 years of age at AF diagnosis and patients with valvular AF (mechanical heart valves or rheumatic/nonrheumatic mitral stenosis).…”
Section: Study Population and Definition Of Frailtymentioning
confidence: 99%
“…9 Physician concerns regarding cognitive impairment, tendency to fall, and polypharmacy may be influential for withholding OAC therapy. 7,10 The treatment decision is further challenged by lack of adequate evidence for the net clinical benefit (NCB) of OAC in frail patients with AF, who have been underrepresented in the randomized trials. Observational studies have demonstrated an NCB in favor of OAC even in octogenarians 11–13 but at the same time indicate that the NCB diminishes with advancing age.…”
mentioning
confidence: 99%
“…Third, atrial brillation, a comorbidity on admission, emerged as an associated factor for longer hospital stay in patients undergoing TKA. In a previous study, multivariate analysis of the length of hospital stay in patients with comorbid atrial brillation reported acute coronary syndrome, acute decompensated heart failure, infection, heart failure with reduced ejection fraction (HFrEF), heart failure with preserved ejection function (HFpEF), elevated N-terminal (NT)-pro hormone brain natriuretic peptide (NT-proBNP) levels, and elevated combination of hypertension, abnormal liver/renal function, stroke history, bleeding history or predisposition, labile international normalized ratio, old age and drug/alcohol usage (HAS-BLED) as predictors of longer hospital stay 25 . In addition, frailty is common in patients with atrial brillation, which possibly impacts therapies and outcomes 26,27 .…”
Section: Related Factors Affecting the Length Of Hospital Staymentioning
confidence: 99%